Ectopic Cushing's syndrome in a patient with inferior petrosal sinus sampling indicating pituitary‐dependent ACTH secretion. Issue 1 (14th December 2019) - Micko, Alexander; Wolfsberger, Stefan; Knosp, Engelbert; Marik, Wolfgang; Haberler, Christine; Winhofer, Yvonne; Luger, Anton; Vila, Greisa
Abstract: In an unclear case of Cushing's syndrome, IPSS identifies the origin of ACTH secretion, and together with MRI enables the localization of an ectopic corticotroph adenoma in the parasellar or cavernous sinuses region. Abstract : In an unclear case of Cushing's syndrome, IPSS identifies the origin of ACTH secretion, and together with MRI enables the localization of an ectopic corticotroph adenoma in the parasellar or cavernous sinuses region.